Fiber reinforced composites in prosthodontics - A systematic review - Sanjna Nayar; R Ganesh; S Santhosh (Wolters Kluwer Medknow Publications, 2015)
Fiber-reinforced composite (FRC), prostheses offer the potential advantages of optimized esthetics, low wear of the opposing dentition and the ability to bond the prosthesis to the abutment teeth, thereby compensating for less-than-optimal abutment tooth retention and resistance form. These prostheses are composed of two types of composite materials: Fiber-composites to build the substructure and hybrid or micro fill particulate composites to create the external veneer surface. This article reviews the various types of FRCs and its mechanical properties.